Characterisation of Danish agricultural investments in Tanzania and Uganda: Presentation of six cases of agricultural investments and their intended development outcomes - Rikke Brandt Broegaard; Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2022)
This DIIS Working Paper presents key characteristics of each of the six cases including main crop focus, size and business model, as well as types of investors, their investment approach and the factors that motivate them. It also presents the different objectives that the investors have expressed wanting to achieve. As most of the investments involve private funds, it is reasonable to expect that one important goal is to ensure a viable economy in the investment. However, in addition to an economically sound investment, all of the investors behind these six cases have ambitions regarding ways in which they see themselves - through the investment - as contributors towards a positive societal development in the area of the investment. Thus, the paper presents the different ways the investors see their investments contributing to development in the area. The paper is based on interviews with the investors and field work in the areas of investments.
Keywords: 330; agriculture; development finance; capital fund; Kanungu; Karatu; Iringa; Njombe; Nwoya; Nakasongola; coffee farms